2022
DOI: 10.7717/peerj.13678
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia was higher in women than in men: a cross-sectional study from a rural area in eastern China

Abstract: Background There were limited studies specifically evaluating whether the difference of the prevalence of sarcopenia exists in men and women in older adults from rural areas in China. The aim of this study was to compare the prevalence of sarcopenia between men and women in a rural area in eastern China and to explore the underlying causes. Methods This study included 1,105 participants aged 60-89 years. Muscle mass was measured by bio-elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
10
1
1
Order By: Relevance
“…This corresponds to findings from studies by Yuenyongchaiwat et al 38 and Chew et al 66 Another study by Du et al 67 conducted among 631 subjects supported this statement by stating that levels of testosterone and insulin‐like growth factor‐1 levels decreased significantly in older males, which caused rapid loss of muscle mass and strength compared to their female counterparts. However, Wang et al 56 and Samper‐Ternent et al 49 from the current study reported otherwise, stating that the prevalence of sarcopenia among females was higher than in males, and there were also other studies supporting this outcome 68,69 . Older women experience menopause, which causes hormonal changes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This corresponds to findings from studies by Yuenyongchaiwat et al 38 and Chew et al 66 Another study by Du et al 67 conducted among 631 subjects supported this statement by stating that levels of testosterone and insulin‐like growth factor‐1 levels decreased significantly in older males, which caused rapid loss of muscle mass and strength compared to their female counterparts. However, Wang et al 56 and Samper‐Ternent et al 49 from the current study reported otherwise, stating that the prevalence of sarcopenia among females was higher than in males, and there were also other studies supporting this outcome 68,69 . Older women experience menopause, which causes hormonal changes.…”
Section: Discussionmentioning
confidence: 51%
“…However, Wang et al 56 and Samper-Ternent et al 49 from the current study reported otherwise, stating that the prevalence of sarcopenia among females was higher than in males, and there were also other studies supporting this outcome. 68,69 Older women experience menopause, which causes hormonal changes. Oestradiol can promote muscle regeneration, but ageing causes a decline in oestradiol levels, while simultaneously increasing visceral adiposity and decreasing bone density, muscle mass and strength.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, protein consumption should be performed in close proximity to exercise. [27][28][29][30] The MLgR model that is depicted in figure 1 demonstrates that there is a clear exponential relationship between the fBMDs of the patients who are being investigated and the probabilities that they have a higher functionality status. The MLgR illustrated model was displaced to the right when the patients' co-morbidity burden (AACCI) reached or surpassed 4.…”
Section: Discussionmentioning
confidence: 99%

Importance of bone mineral density and comorbidity index for functionality

Rania Farhan Hamdan Khreisat,
Eman Farhan Hamdan Khreisat,
Majd Yaser Salem Abu Hammour
et al. 2024
World J. Bio. Pharm. Health Sci.
“…Several epidemiological studies on sarcopenia in patients with HF have indicated a lower prevalence of sarcopenia in males than in females. [27][28][29][30] However, the results of the MA published in 2021…”
Section: Discussionmentioning
confidence: 99%